Identification of a Rare PSEN1 Mutation (Thr119Ile) in Late-Onset Alzheimer’s Disease With Early Presentation of Behavioral Disturbance - Zhang, Shouzi; Li, Xiang; Zhang, Li; Meng, Xiangyan; Ma, Li; Zhang, Guangze; Wu, Haiyan; Liang, Ling; Cao, Meng; Mei, Fan (Frontiers in Psychiatry, 2020)
Alzheimer’s disease (AD) is the most common form of neurodegenerative dementia. In this study, whole genome sequencing identifies one rare and likely pathogenic mutation (c.356C>T, p.T119I) in presenilin 1(PSEN 1) associated with a frontal variant of AD. Affected individuals in the kindred developed late-onset cognitive decline accompanied with early presentation of psychiatric symptoms. Positive amyloid PiB PET tracing suggested presence of pathophysiological biomarker for AD. Whole genome sequencing analysis evaluated rare coding mutations in susceptible genes for various types of dementia and supported the role of PSEN1 as a causal gene. Identification of this T119I variant in PSEN1 might broaden the spectrum of genetic basis and clinical diversity of familial AD.